Synthesis of single cell oil from crude glycerol: a systematic literature review (Research, Society and Development, 2022)
Biodiesel has been an important energy alternative for reducing the emission of polluting gases, however, vegetable oils and animal fats used as raw materials for its synthesis have restrictions that limit the production process. This work is a systematic literature review that discusses possible applications for the reuse of crude glycerol from the transesterification of vegetable oil or animal fat from biodiesel production. Thus, we present some microorganisms that may be used in the production of microbial oil (single cell oil) from crude glycerol. The yeasts Rhodotorula mucilagenosa and Rhodosporidium toruloides, with lipid content of 65% and 64%, respectively, and the filamentous fungus Mortierella isabellina with 66%, are potential producers of single cell oil. In M. isabelina, the stored lipids are mostly neutral, in addition, its total composition of fatty acids presents remarkable similarities with Brassica napus oil, an excellent oil for biodiesel production. The fatty acid profile for R. mucilagenosa is rich in oleic acid (61.88%), linoleic acid (16.17%), and linolenic acid (1.03%) comprising ~80% monounsaturated fatty acids and fatty acids polyunsaturated fats from total lipids. In R. toruloides, the fatty acid profiles of the lipids are similar to Jatropha curcas oil, a raw material widely used for the production of biodiesel. Overall, it is expected that this review will stimulate the development of new processes, mainly for the destination of crude glycerol from the biofuel chain in single cell oil.